2015
DOI: 10.1007/s10552-015-0546-z
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual and reproductive history and use of exogenous sex hormones and risk of thyroid cancer among women: a meta-analysis of prospective studies

Abstract: Menstrual and reproductive factors may play a role in the etiology of thyroid cancer, possibly through the mediation of estrogen receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 55 publications
2
39
0
3
Order By: Relevance
“…Similarly, a population-based case–control study carried out in the USA showed a transiently increased risk of PTC among women who had delivered a live birth within the 5 years before the reference date, and the risk was even more pronounced among women with two or more births (OR 4.2, 95% CI 2.0–8.9) compared to women with one pregnancy only (OR 1.6, 95% CI 1.0–2.7) (15). A short-term effect of pregnancy on thyroid cancer risk is also supported by pooled estimates of large datasets (32, 34, 52, 53) and findings from other studies (16–18, 27, 31, 54). However, other investigations concluded that ever being pregnant, number of births and/or recency of pregnancies resulted in no increased (23, 26) or even decreased (22) risk of DTC (Table 2).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Similarly, a population-based case–control study carried out in the USA showed a transiently increased risk of PTC among women who had delivered a live birth within the 5 years before the reference date, and the risk was even more pronounced among women with two or more births (OR 4.2, 95% CI 2.0–8.9) compared to women with one pregnancy only (OR 1.6, 95% CI 1.0–2.7) (15). A short-term effect of pregnancy on thyroid cancer risk is also supported by pooled estimates of large datasets (32, 34, 52, 53) and findings from other studies (16–18, 27, 31, 54). However, other investigations concluded that ever being pregnant, number of births and/or recency of pregnancies resulted in no increased (23, 26) or even decreased (22) risk of DTC (Table 2).…”
Section: Resultssupporting
confidence: 55%
“…More recently, two meta-analyses showed postmenopausal status and older age at menopause to be, respectively, associated with a borderline significant reduction (RR 0.79, 95% CI 0.62–1.01) (32) and increase (RR 1.24, 95% CI 1.00–1.53) (33) of DTC risk. A further meta-analysis focusing on PTC only, also found late age at menopause to be associated with increased PTC risk (RR = 1.39, 95% CI 1.03–1.89) (34).…”
Section: Resultsmentioning
confidence: 99%
“…The role of estrogens in the development and evolution of DTC has been widely analyzed in several studies [20,21,22,23,24,25,26,27,28]. A recent meta-analysis including >5,000 patients reported that menopausal women had a reduced thyroid cancer risk, whereas increasing age at first pregnancy/birth was associated with a higher cancer risk [29]. Similar to other epithelial tumors, DTC also expresses both ER isoforms, with ER-α activation being associated with increased estrogen-dependent cell proliferation and, in contrast, ER-β likely promoting apoptotic actions and other suppressive functions in thyroid tumors [22,30,31,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Based on epidemiological data, it has long been proposed that hormonal factors may determine or modulate the risk of thyroid cancer. Indeed, thyroid cancers are threefold more frequent in women than in men after puberty and incidence decreases after menopause . A role of female hormones in the aetiology of thyroid cancer has been suggested with a direct action of oestrogens, via its receptors (ER), on proliferative and neoplastic disorders .…”
Section: Introductionmentioning
confidence: 99%